1984-1985 ネン マクマードサウンド チイキ ノ コクサイ キョウドウ カンソク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1985)
P(論文) 1984-1985年のマクマード地域の国際共同観測は, 第5年目を迎えた「エレバス火山国際地震研究(IMESS)」とこれからの国際共同観測の予察として, 捕獲岩の採集を主目的とした地質調査を実施した。日本からは神沼克伊, 渋谷和雄(国立極地研究所)と新井田清信(北海道大学理学部)の3名が参加した。日本隊は例年通りテレメータ観測網の記録系の保守, 観測した磁気テープの再生, 読み取りを担当した。更に本シーズンの主目的の人工地震観測に際しては7点の臨時地震観測点を設置して観測にあたった。テレメータ観測網, 臨時観測網の刻時精度をあげるため人工衛星受信装置をスコット基地に設置して, 時間を記録した。地質調査はバーンズ岬, バード岬, クロージア岬, ブラック島, タートロックなどで実施した。また各地震観測点からも岩石標本を採集した。新しく5点で重力測定をしたほか, 各地震観測点での再測も実施した。 Continuous seismic observations have been carried out since December 1980 by a cooperative International Mount Erebus Seismological Studies (IMESS) which includes Japan, the United States and New Zealand. Three Japanese participating in the IMESS visited McMurdo Station during the 1984-1985 field season. They were K. KAMINUMA and K. SHIBUYA (National Institute of Polar Research), and K. NIIDA (Faculty of Science, Hokkaido University). They conducted a series of scientific research programs during their tenure at McMurdo Station from 11 November 1984 to 15 January 1985. 1. Seismic observation by the telemetry network : Japanese scientists played back the magnetic tapes which have recorded since September 1984. The daily frequencies of eruptions and volcanic earthquakes occurring in and around Mount Erebus were counted and earthquakes were scaled. 2. Explosion seismic experiments : From 3 to 26 December 1984 seven seismic stations were established on the summit and the flank of Mount Erebus for the explosion seismic experiments and for precise determination of earthquake locations. 3. Gravity : Five new gravity stations were established on Ross Island during the 1984-1985 field season. 4. Geological survey : In order to enhance the study of the structure of the McMurdo volcanoes using both geophysical and geological methods, geological surveys were also carried out. Field studies were made on the volcanic rocks and the xenoliths of Cape Bird, Cape Crozier, Hut Point Peninsula and Black Island. departmental bulletin paper